Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Lê Ngọc Uyển Linh

Số nguyên x thỏa mãn x-(-25-7-2x)=6+x là x= 

Nguyễn Ngọc Quý
8 tháng 1 2016 lúc 20:04

x - (-25 - 7 - 2x) = 6 + x

x - (-32 - 2x ) = 6 + x

3x + 32 = 6 + x

x - 3x = 32 - 6

-2x = 26

x = -13 

 

Mai Ngọc
8 tháng 1 2016 lúc 20:05

x-(-25-7-2x)=6+x

=>x+25+7+2x=6+x

=>3x+32=6+x

=>2x=-26

=>x=-13

vũ thu trang
8 tháng 1 2016 lúc 20:26

    x-(-25-7-2x)=6-x

=>x+25+7+2x=6-x

    x+2x+x       =-25-7+6

        4x           =  -26

          x           =-6,5

        Vậy...................

                                     Nhớ tik mk nha!

 

Nguyễn Tiến Đạt
8 tháng 1 2016 lúc 21:11

x - (-25 - 7 - 2x) = 6 + x

x - (-32 - 2x ) = 6 + x

3x + 32 = 6 + x

x - 3x = 32 - 6

-2x = 26

x = -13 


Các câu hỏi tương tự
Nguyễn Hoàng Thảo Ly
Xem chi tiết
Công_chúa_Sofia
Xem chi tiết
Nguyễn Mạnh Trung
Xem chi tiết
Nguyễn Vũ Ngọc Nhi
Xem chi tiết
Dương Helena
Xem chi tiết
ko can biet ten
Xem chi tiết
Trần Lê Huy Bình
Xem chi tiết
Ho Thanh Vinh
Xem chi tiết
phammiahnh
Xem chi tiết